2017
DOI: 10.11138/mltj/2017.7.3.449
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of patellar tendon size and structure in asymptomatic professional players: sonographic study

Abstract: SummaryBackground: Ultrasonographic abnormalities of the patellar tendon frequently occur in asymptomatic athletes and it is not always clear whether they precede (and may predict) the development of tendinopathy. Objective: This study aimed to investigate by ultrasonography the prevalence of patellar tendon abnormalities in players of "pallapugno" and to establish whether structural tendon abnormalities predict tendinopathy development. Methods: Ultrasound B-mode images of the patellar tendon of both sides we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…For the purpose of this texture-analysis study, 6 images on each side were analyzed as reported in Table 1. The remaining 4 images on each side were employed also for qualitative assessments of neovascularization and tendon structure as reported in [23]. According to the definition as cited in the Introduction [23], 5 subjects out of the 14 were found to be affected by subclinical tendinopathy (i.e., 5 subjects demonstrated the presence of light structural changes in association with at least mild neovascularization or moderate/severe structural changes with/without neovascularization).…”
Section: Ultrasound Image Acquisition and Protocolmentioning
confidence: 99%
See 4 more Smart Citations
“…For the purpose of this texture-analysis study, 6 images on each side were analyzed as reported in Table 1. The remaining 4 images on each side were employed also for qualitative assessments of neovascularization and tendon structure as reported in [23]. According to the definition as cited in the Introduction [23], 5 subjects out of the 14 were found to be affected by subclinical tendinopathy (i.e., 5 subjects demonstrated the presence of light structural changes in association with at least mild neovascularization or moderate/severe structural changes with/without neovascularization).…”
Section: Ultrasound Image Acquisition and Protocolmentioning
confidence: 99%
“…Morphological abnormalities in the tendon ultrasound image, such as increased tendon thickness, neovascularization, and presence of hypoechoic areas, have also been found in a large percentage of asymptomatic athletes [9,11,13,22]. Recently, Giacchino et al [23] also conducted a study of patellar tendon size and structure in throwers and found that the prevalence of subclinical tendinopathy was high in the non-dominant patellar tendon as a possible result of the repeated non-dominant lower limb overload. To do so, the authors arbitrarily defined subclinical tendinopathy as "the presence of either light structural changes in association with at least mild neovascularization or moderate/severe structural changes with/without neovascularization" [23].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations